Statistics - Donnelly, Robert A., Jr; Abdel-Raouf, Fatma (Idiot's guides., 2016)
Statistics is a class that is required in many college majors, and it's an increasingly popular Advanced Placement high school course. In addition to math and technical students, many business and liberal arts students are required to take it as a fundamental component of their majors. A knowledge of statistical interpretation is vital for many careers. Idiot's Guides: Statistics explains the fundamental tenets in language anyone can understand. Content includes: - Calculating descriptive statistics - Measures of central tendency: mean, median, and mode - Probability - Variance analysis - Inferential statistics - Hypothesis testing - Organizing data into statistical charts and tables.